PSICO-PHYSICAL REPERCUSSIONS OF THE RESISTED TRAINING (Fiep Bulletin - online, 2013)
The aims of this study were to reflect about the relationship between mind and body within physical activity, under a Reich's perspective and discuss the approach of resisted training towards a transdisciplinary attitude. The methodology chosen was qualitative: systematic bibliographic review. The following themes have been discussed: the relationship between mind and body within Reich's perspective; the approach of resisted training towards a transdisciplinary attitude. There was an attempt of dealing with the subject in his peculiarity, as a whole, considering possible obstacles that avoid vital energy flow. It is important the adoption of a transdisciplinary attitude in order to manage with the client's different dimensions, thus promoting human and integrated actions towards well-being promotion.
Keywords: psychology; physical education; body